The potential of learning with (and not from) artificial intelligence in education - Chichekian, Tanya; Benteux, Bérenger (Frontiers in Artificial Intelligence, 2022)
AI-powered technologies are increasingly being developed for educational purposes to contribute to students’ academic performance and overall better learning outcomes. This exploratory review describes how the effectiveness of AI-driven technologies are being measured, as well as the roles attributed to teachers, and the theoretical and practical contributions derived from the interventions. Findings from 48 articles highlighted that learning outcomes were more aligned with the optimization of AI systems, mostly nested in a computer science perspective, and did not consider teachers in an active role in the research. Most studies proved to be atheoetical and practical contributions were limited to enhancing the design of the AI system. We discuss the importance of developing complementary research designs for AI-powered tools to be integrated optimally in education.